Subtrochanteric Fracture following Removal of a Porous Tantalum Implant - Derek F. Amanatullah; Randall Farac; Thomas J. McDonald; H. David Moehring; Paul E. Di Cesare (Case Reports in Orthopedics)
Osteonecrosis of the hip accounts for about 10% of all total hip arthroplasty cases and presents a significant challenge for those patients with and without femoral head collapse. Subtrochanteric femur fractures have been reported with numerous types of proximal femoral implants. Care must be taken to avoid penetrating the lateral cortex of the proximal femur inferior to the distal border of the lesser trochanter. Core decompression requires a 3 mm to 20 mm defect in the lateral femoral cortex. Subtrochanteric femur fractures are a well-known complication of core decompression as well. We present a case of a subtrochanteric fracture following the removal of a porous tantalum implant.